2021
DOI: 10.3390/clockssleep3010004
|View full text |Cite
|
Sign up to set email alerts
|

Disorders of Arousal: A Chronobiological Perspective

Abstract: Non-rapid eye movement (NREM) sleep parasomnias are characterized by motor and emotional behaviors emerging from incomplete arousals from NREM sleep and they are currently referred to as disorders of arousal (DoA). Three main clinical entities are recognized, namely confusional arousal, sleep terror and sleepwalking. DoA are largely present in pediatric populations, an age in which they are considered as transitory, unhabitual physiological events. The literature background in the last twenty years has extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…The results of our work confirm the view of NREM parasomnias as a complex state, with intermingled features of both wakefulness and SWS. Sleep as a local phenomenon has been demonstrated also in normal subjects, reinforcing the consideration that DoA patients embody the ultimate deregulation of a dysfunctional arousal process, where the tip of the iceberg is the clinical motor episode, 59 with evidence of the coexistence of wake-like and sleep-like activity even in the same areas. 17 The presence of broadband alterations with a specific local topographic distribution in the pre-episode disclosed in our study might provide diagnostic utility as well as a deeper understanding of DoA networks and pathophysiology.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The results of our work confirm the view of NREM parasomnias as a complex state, with intermingled features of both wakefulness and SWS. Sleep as a local phenomenon has been demonstrated also in normal subjects, reinforcing the consideration that DoA patients embody the ultimate deregulation of a dysfunctional arousal process, where the tip of the iceberg is the clinical motor episode, 59 with evidence of the coexistence of wake-like and sleep-like activity even in the same areas. 17 The presence of broadband alterations with a specific local topographic distribution in the pre-episode disclosed in our study might provide diagnostic utility as well as a deeper understanding of DoA networks and pathophysiology.…”
Section: Discussionmentioning
confidence: 53%
“…DoA patients, conversely, appear mentally sleeping but physically awake, a response which embodies at the same time the double nature of the arousal. 59 Among studies focused on the pre-arousal activity in DoA ( Table 1 ), only few included controls and showed a higher spectral power in delta band before DoA episodes, 19–21 suggesting a greater difficulty in fully awakening in DoA. However, homogeneous studies directly comparing DoA and healthy subjects are lacking and potential differences in the pre-arousal period should be searched in the presence of topographic distribution, different power of EEG bands, along with differences in connectivity pathways.…”
Section: Discussionmentioning
confidence: 99%
“…During SW, patients leap out of bed and wander about the room or the house, or more rarely, may even walk outside. SW patients may perform routine activities like dressing, washing, preparing for school, urinating (sometimes at inappropriate locations), but can also engage in more dangerous actions like moving the furniture, manipulating sharp objects, or jumping out a window [ 1 , 11 , 12 , 13 , 14 , 15 ]. Prolonged cases associated with sleep driving have been described [ 16 ].…”
Section: Diagnosis Of Doamentioning
confidence: 99%
“…Classically, DoA are intended to be based on a genetic predisposition, on which priming factors influencing the homeostasis of SWS as well as precipitating factors such as apnea, noise or touch produce the episodes [6]. Unresolved priming factors, perpetuating in adulthood, might lead to the persistence of the episodes [8]. Prospective studies with a long follow-up are essential to depict the natural history of NREM parasomnias and the possible factors leading to a better or worse prognosis.…”
Section: Real Picture or More Severe Phenotypes?mentioning
confidence: 99%
“…Over the years, both epidemiologic and clinical reports from tertiary adult sleep centers have shown that DoA might persist in adulthood, appear de novo in some cases or even last through elderly life [7]. These aspects have led to the suggestion of a fourth P, i.e., "perpetuating" factors, responsible for the persistence of DoA throughout the life span [8]. Long follow-up studies are lacking for DoA, so several aspects have not been unraveled yet.…”
Section: Introductionmentioning
confidence: 99%